PENERAPAN FRAMEWORK CODEIGNITER UNTUK WEBSITE TOKO ONLINE PADA DASTER HITS PONTIANAK - Sindika Alifia Palma; Sandy Kosasi (P3M STMIK Profesional Makassar, 2023)
Daster Hits pontianak has a need to expand its market share and manage valid data systems. The sales system currently used is traditional sellers and social media such as Instagram and WhatsApp, therefore the interaction between the store and customers is still limited, recording of transactions is still manual using a transaction book, and if customers want to find products they have to scroll Instagram or come directly to the store. The purpose of this research is to apply the CodeIgniter framework to build an online shop website which is expected to help the shop in promoting the product, manage product data, and expedite the product sales process. The research method used in this research is Design Science Research and the design method uses Extreme Programming. The system modeling used is the Unified Modeling Language (UML) and the software testing method uses white-box testing. The advantages of Daster Hits Pontianak Online Shop website are the features such as managing user profiles, product sales, detailed product information, online product orders and payment confirmation, searches using sequential search algorithms, managing product stocks using the Apriori algorithm, and notifications using push notifications. The process of making this program uses the PHP programming language and the MariaDB database.